2018
DOI: 10.5826/10.5826/dpc.0804a06
|View full text |Cite
|
Sign up to set email alerts
|

Onychoscopy: an observational study in 237 patients from the Kashmir Valley of North India

Abstract: Background: Nail disorders comprise approximately 10% of all dermatological conditions. Because diagnosis is not always possible by clinical means alone, additional diagnostic procedures may be required at times. Dermoscopy of nails (onychoscopy) has shown promising results in diagnosing various nail disorders and also avoids time-consuming investigations such as culture and biopsy. Objective: To study the dermoscopic features of various nail disorders to determine the correlation between KOH examination and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 25 publications
6
16
1
Order By: Relevance
“…Spiked and jagged edges were the most common finding in our study, which is similar to study by Bhat et al,[ 11 ] and in contrast to other studies where longitudinal streak was the most common finding. [ 12 13 14 ] Spikes are due to the nail anatomy and fungal invasion.…”
Section: Discussionsupporting
confidence: 92%
“…Spiked and jagged edges were the most common finding in our study, which is similar to study by Bhat et al,[ 11 ] and in contrast to other studies where longitudinal streak was the most common finding. [ 12 13 14 ] Spikes are due to the nail anatomy and fungal invasion.…”
Section: Discussionsupporting
confidence: 92%
“…7 In another study conducted by Bhatt YJ et al on dermoscopy of nail findings they found longitudinal and transverse ridging in 85% and 54% cases respectively which is higher than our study. 8 So from our study, we infer that there is not much difference in clinical and dermatoscopic finding in these nail surface changes.…”
Section: Discussionmentioning
confidence: 51%
“…Nakamura et al performed dermoscopy in 500 cases of nail dystrophies and found chromonychia, onycholysis, opacity, and longitudinal stripes in patients with OM (1). In another study with onychoscopy in 237 patients with nail disorder, OM showed jagged pattern of the proximal margin of the onycholytic area, spikes in the proximal fold, white-yellow longitudinal striae in the onycholytic nail plate, and distal irregular termination pattern (12).…”
Section: Discussionmentioning
confidence: 92%